2017
DOI: 10.1111/vox.12549
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of bleeding with tranexamic acid in a series of 12 patients with immune thrombocytopenia

Abstract: We recommend the use of TA in ITP patients with bleeding and/or an increased bleeding risk. Ultimately, cessation of bleeding plays a key role in the management of such affected patients. However, future studies are required to optimize dose and administration routes (intravenous or oral).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…1,2 And while TXA has been studied in adults, with anecdotal evidence of its use in controlling mucosal bleeding, and a case TXA in Life-threatening Nontraumatic Hemorrhage in ITP series describing its use of TXA in chronic ITP-related bleeding, there are no studies in children. [4][5][6] When reviewing the literature, we found that TXA has been studied and used in a wide range of settings, especially in the surgical fields including orthopedic procedures, otolaryngologic surgery, obstetric bleeding and heavy menstrual bleeding, pediatric cardiac surgery, and coronary artery surgery. 2,[8][9][10][11] A large meta-analysis evaluating TXA in surgical patients showed that TXA reduced the need for blood transfusion and resulted in fewer deaths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 And while TXA has been studied in adults, with anecdotal evidence of its use in controlling mucosal bleeding, and a case TXA in Life-threatening Nontraumatic Hemorrhage in ITP series describing its use of TXA in chronic ITP-related bleeding, there are no studies in children. [4][5][6] When reviewing the literature, we found that TXA has been studied and used in a wide range of settings, especially in the surgical fields including orthopedic procedures, otolaryngologic surgery, obstetric bleeding and heavy menstrual bleeding, pediatric cardiac surgery, and coronary artery surgery. 2,[8][9][10][11] A large meta-analysis evaluating TXA in surgical patients showed that TXA reduced the need for blood transfusion and resulted in fewer deaths.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 And while TXA has been studied in adults, with anecdotal evidence of its use in controlling mucosal bleeding, and a case series describing its use of TXA in chronic ITP-related bleeding, there are no studies in children. 4 6 …”
Section: Discussionmentioning
confidence: 99%
“…Antifibrinolytics (tranexamic acid and aminocaproic acid) are successfully used to control significant bleeding in patients with ITP [102][103][104]. Oral contraceptives can be used in female patients with menorrhagia.…”
Section: Treatment Of Active Bleedingmentioning
confidence: 99%
“…Drugs that may be useful in patients with ITP to control minor bleeding are tranexamic acid (particularly for mucocutaneous bleeds) and contraception (menorrhagia). 45,46 In life-threatening ITP bleeding emergencies, recombinant activated factor VII may be a useful supportive treatment.…”
Section: Treatments Active Bleedingmentioning
confidence: 99%
“…Tranexamic acid is described in two studies as highly effective in controlling menorrhagia and acute bleeding in female patients with ITP and should be taken into account in the treatment of female patients with chronic ITP. 45,46…”
Section: Immunomodulatorsmentioning
confidence: 99%